Black Star, Crescent Moon : the Muslim International and Black Freedom beyond America - Daulatzai, Sohail (University of Minnesota Press, 2012)
"The same rebellion, the same impatience, the same anger that exists in the hearts of the dark people in Africa and Asia," Malcolm X declared in a 1962 speech, "is existing in the hearts and minds of 20 million black people in this country who have been just as thoroughly colonized as the people in Africa and Asia." Four decades later, the hip-hop artist Talib Kweli gave voice to a similar Pan-African sentiment in the song "K.O.S. (Determination)": "The African diaspora represents strength in numbers, a giant can't slumber forever.". Linking discontent and unrest in Harlem and Los Angeles to a